DEMYSTIFYING ISLAMOPHOBIA : TOWARDS A DEEPER UNDERSTANDING OF ISLAM - Mohd Farid Mohd Shahran; Muhammad Syafiq Bohannuddin (Khayra Ummah Series (No.8/9), 2023)
This volume is part of the Khayra Ummah series, being itself the culmination of a sequence of colloquium of several themes organized by IKIM. The issues addressed in this series are: Islamic economics; Islamophobia; governance; moral deterioration; disruptive technology; environmental degradation; and the Islamic mind.